Process of Preparation of Future Technology Teachers for Innovative Activity (Eurasian Journal of Engineering and Technology, 2022)
The article analyzes the structure and content of the innovative activities of the future teacher of "Technology" in the new conditions, as well as the analysis of "Science" science, production, economy, management, development of innovative processes in society. gave